PERANAN SEKTOR INDUSTRI TERHADAP PEREKONOMIAN KABUPATEN PASANGKAYU - Darmawan, I Made; Ali, H. Amar; Jokolelono, Eko (Katalogis, 2021)
The purpose of this research is to find out and identify: 1) The contribution of the industrial sector to the economy of Pasangkayu Regency. 2) Sectors that are the basic sectors in the economy of Pasangkayu Regency. This type of research is quantitative with contribution analysis and Location Quotient (LQ) analysis techniques. The results of the study that the results of the analysis of the contribution provided by the industrial sector to the formation of the Pasangkayu Regency GRDP in 2013-2018 amounted to 28.74%. LQ analysis shows that the Pasangkayu Regency industrial sector from 2013-2018 became a base sector with an LQ value of 2.67. Distribution of industries focused in Pasangkayu District which is the capital of Pasangkayu Regency and several other districts.